Effects of temperature and void on the dynamics and microstructure of structural transition in single crystal iron. (25th May 2018) - Shao, Jian-Li; Wang, Pei; Zhang, Feng-Guo; He, An-Min
Abstract: With classic molecular dynamics simulations, we investigate the effects of temperature and void on the bcc to hcp/fcc structural transition in single crystal iron driven by 1D ([0 0 1]) and 3D (uniform) compressions. The results show that the pressure threshold does not reduce monotonously with temperature. The pressure threshold firstly increases and then decreases in the range of 60–360 K under 1D compression, while the variation trend is just opposite under 3D compression. As expected, the initial defect may lower the pressure threshold via heterogenous nucleation. This effect is found to be more distinct at lower temperature, and the heterogenous nucleation mainly results in hcp structure. Under the condition of strain constraint, the products of structural transition will respectively form flaky hcp twin structure ((1 0 0) or (0 1 0)) and lamellar structure (1 1 0) of mixed phases under 1D and 3D compressions. During the structural transition, we find the shear stress (1D compression) of hcp phase is always lower than that of bcc phase. The cold energy calculations indicate that the hcp phase is the most stable under high pressure. However, we observe the evident metastable state of bcc phase, whose energy will be much higher than both hcp and fcc phases, and then provides the possibility for the occurrence of fcc nucleation.